2014
DOI: 10.1155/2014/215763
|View full text |Cite
|
Sign up to set email alerts
|

The Soluble Form of CTLA-4 from Serum of Patients with Autoimmune Diseases Regulates T-Cell Responses

Abstract: Cytotoxic T lymphocyte associated antigen-4 (CTLA-4) is a costimulatory receptor transducing a potent inhibitory signal. Increasing evidence showed that CTLA-4 gene is an important susceptibility locus for autoimmune disorders. Alternatively spliced mRNA generates a soluble form, called sCTLA-4. Whereas low levels of sCTLA-4 are detected in normal human serum, increased/high serum levels are observed in several autoimmune diseases. The biological significance of increased sCTLA-4 serum level is not fully clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Strikingly, 11 out of the 18 sICPs examined here were down-regulated in patients with AH. Most of the 11 sICPs, including four inhibitory ICPs (BTLA, CTLA-4, LAG-3, and PD-1) and three stimulatory ICPs (GITR, CD80, and ICOS), are generated through mRNA alternative splicing and secretion, (16,28,29) whereas sCD28, sCD160, sPD-L1 are cleaved from membrane-bound counterparts. (23)(24)(25) Consistent with their hyperactivated state, T cells from patients with AH expressed high levels of membrane-bound inhibitory ICPs, including CTLA4, LAG-3 and PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, 11 out of the 18 sICPs examined here were down-regulated in patients with AH. Most of the 11 sICPs, including four inhibitory ICPs (BTLA, CTLA-4, LAG-3, and PD-1) and three stimulatory ICPs (GITR, CD80, and ICOS), are generated through mRNA alternative splicing and secretion, (16,28,29) whereas sCD28, sCD160, sPD-L1 are cleaved from membrane-bound counterparts. (23)(24)(25) Consistent with their hyperactivated state, T cells from patients with AH expressed high levels of membrane-bound inhibitory ICPs, including CTLA4, LAG-3 and PD-1.…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct isoforms have been identified: the full‐length isomer, a transmembrane protein found primarily on T‐cells (CTLA‐4), and the soluble monomeric protein that is secreted extracellularly (sCTLA‐4). sCTLA‐4 has been linked to immune cell dysregulation with elevated levels of blood sCTLA‐4 reported in patients with thyroid disease, type I diabetes, SLE, myasthenia gravis, and celiac disease . Similarly, patients with lower airway inflammation have showed elevated levels of blood sCTLA‐4 .…”
Section: Discussionmentioning
confidence: 99%
“…sctla4 mRNA levels were also correlated with worsening objective and subjective disease severity measures (Tables and ), showing that increased expression of sctla4 is associated with increased disease severity and worse QOL. Previous research has identified sCTLA‐4 in the blood as a potential biomarker for inflammatory diseases, such as autoimmune thyroiditis (AIT), celiac disease, and prostatitis due to the positive correlation of sCTLA‐4 in the blood with clinical markers of disease . Similarly, the correlation of sctla4 with clinical measures of disease severity in CRSsNP make this gene an interesting potential biomarker for CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the gene encoding CTLA‐4 (e.g. rs231775 and rs5742909) and increased serum levels of the soluble form of CTLA‐4 have been associated with dysregulated T‐cell responses and increased susceptibility to COPD and chronic bronchitis . Furthermore, increased levels of soluble CTLA‐4 in the serum of patients with COPD paralleled decreased lung function and increased C‐reactive protein (CRP) .…”
Section: Introductionmentioning
confidence: 99%
“…rs231775 and rs5742909) and increased serum levels of the soluble form of CTLA-4 have been associated with dysregulated T-cell responses and increased susceptibility to COPD and chronic bronchitis. [17][18][19][20] Furthermore, increased levels of soluble CTLA-4 in the serum of patients with COPD paralleled decreased lung function and increased C-reactive protein (CRP). 21 Frequencies of circulating CTLA-4 + T cells and CTLA-4 + Treg cells were also higher in patients with COPD than in controls.…”
Section: Introductionmentioning
confidence: 99%